Killer Activity of Hanseniaspora uvarum Isolated from Dates Vinegar: Partially Purification and Characterization of Killer Toxin (Baghdad Science Journal, 2019)
This study was conducted to isolate and identify killer yeast Hanseniaspora uvarum from dates vinegar and measurement the ability of this yeast to produce killer toxin. The antimicrobial activity of the concentrated supernatant containing partially purified concentrated killer toxin was also detected against several pathogenic bacteria and yeast species, which includes two types of yeast Rhodotorula mucilaginosa and Candida tropicalis and four human pathogenic bacteria Staphylococcus aureus, Escherichia coli, Klebsiella pneumoniae and Pseudomonas aeurginosa. In addition, the antagonistic activity of examined yeast have been studied toward four types of fungi, where two are pathogenic for human Trichophyton mentagrophytes and Trichophyton rubrum and two are plant pathogens Fusarium solani and Sclerotinia sclerotiorum. The results of killer toxin production experiments revealed the ability of yeast to produce killer toxin with molecular weight at 18 kDa by 12 % SDS electrophoresis. The optimal conditions for killer toxin production were studied, and their antimicrobial activity was determined. The results revealed that killer toxin production was increased at 4 % NaCl, the highest inhibtion zone was 20 mm for S. aureus, while the lowest inhibition zone was 7 mm for E. coli. Killer activity was increased at pH 4 and the best inhibtion zone obtained was about 16 mm for K. pneumoniae, while 8 mm for E. coli and C. tropicalis. The temperature was also affect the production of killer toxin, where 25 °C is the best temperature for toxin production of examined yeast, The best killer activity was 21 mm for C. tropicalis. The antagonistic activity of killer yeast H. uvarum toward pathogenic fungal growth was determined and showed killer activity about 61.11, 44.44, 33.33 and 24.44 % against T. mentagrophytes, T. rubrum, F. solani and S. sclerotiorum in comparison to the control.